1985
DOI: 10.1038/315061a0
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of connective tissue cell growth by substance P and substance K

Abstract: Connective tissue cells proliferate actively when cultured in the presence of serum. Platelet-derived growth factor (PDGF), a basic protein of relative molecular mass approximately 30,000, has been identified as the major serum mitogen for these cells; its main physiological/pathophysiological role may be to initiate wound healing in connection with tissue injury. However, growth of cultured cells is also influenced by several other factors, including epidermal growth factor, fibroblast growth factor, insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
252
1
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 655 publications
(270 citation statements)
references
References 22 publications
15
252
1
2
Order By: Relevance
“…Although this could be attributed to physical activity inhibiting new nerve ingrowth in general, this seems less likely given the number of reports showing that sensory neuropeptides increase the proliferation of fibroblasts and endothelial cells. 13,23,24 Therefore, we hypothesize that high physical activity causes an earlier both in-growth and disappearance of nerve fibers from the tendon proper. The disappearance of nerve fibers already at 4 weeks would seem to reflect a more mature stage of healing compared to that noted in freely moving rats in the longitudinal study, in which the disappearance did not occur until much later, that is, between week 8 to 16 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this could be attributed to physical activity inhibiting new nerve ingrowth in general, this seems less likely given the number of reports showing that sensory neuropeptides increase the proliferation of fibroblasts and endothelial cells. 13,23,24 Therefore, we hypothesize that high physical activity causes an earlier both in-growth and disappearance of nerve fibers from the tendon proper. The disappearance of nerve fibers already at 4 weeks would seem to reflect a more mature stage of healing compared to that noted in freely moving rats in the longitudinal study, in which the disappearance did not occur until much later, that is, between week 8 to 16 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11 The two sensory neuropeptides analyzed, that is, substance P (SP) and calcitonine gene related peptide (CGRP), have previously been reported to promote angiogenesis and tissue regeneration, 12,13,15,16,23,26 partly by stimulating proliferation of endothelial cells and fibroblasts. 12,13,23,24 Given that neuropeptides mediate trophic effects, it might prove that the positive effects seen after mechanical stimulation, that is, early mobilization and exercise after tendon injury, is mediated to some extent by the peripheral nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Tachykinin peptides may also act as growth factors [23] or may contribute to local neurogenic inflammation [24]. Since a variety of these biological activities are elicited by all three tachykinin peptides, it is often thought simply that the three peptides all participate in evoking a variety of physiological responses in the CNS and peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Strong pharmacological and physiological evidence indicates that TKs release in the periphery takes place during the well-known phenomenon of 'neurogenic inflammation' (Lembeck & Holzer, 1979; see Chahl, 1988 andHolzer, 1988 for review). Nilsson et al (1985) reported that TKs exert a potent stimulant action on proliferation of human skin fibroblasts and, on this basis, a possible role of endogenous TKs on wound healing was suggested (see also Maggi et al, 1987a;Kjartansson et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…SP, NKA and NKB stimulate preferentially NK,-, NK2-and NK3-receptors, respectively . Nilsson et al (1985) . Recently the task of charactert Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%